Association of lipid, inflammatory, and metabolic biomarkers with age at onset for incident cardiovascular disease - Xue Tian; Shuohua Chen; Yingting Zuo; Yijun Zhang; Xiaoli Zhang; Qin Xu; Yanxia Luo; Shouling Wu; Anxin Wang (BMC Medicine, 2022)
Abstract Background Risk profiles for premature cardiovascular disease (CVD) are unclear. This study aimed to examine baseline risk profiles for incident CVD by age at onset in Chinese population. Methods A total of 97,841 participants without CVD were enrolled from the Kailuan cohort study. Four age groups were examined (< 55, 55 to < 65, 65 to < 75, and ≥ 75 years) for CVD onset. Risk profiles included clinical, lipid, metabolic, and inflammatory risk factors and biomarkers. Results Of the clinical factors, diabetes was associated with the highest relative risk for incident CVD in participants younger than 55 years (sub-distributional hazard ratio [sHR], 4.08; 95% confidence interval [CI], 3.47–4.80). Risk factors that were also noted for CVD onset in participants younger than 55 years included hypertension, metabolism syndrome, overweight or obese, dyslipidemia, and smoking. Among the biomarkers, insulin resistance measured by triglyceride-glucose index had the highest sHR (1.42; 95% CI, 1.35–1.49) for CVD in participants younger than 55 years. In comparison, weaker but significant associations with CVD in participants younger than 55 years were noted for most lipids, metabolic biomarkers, and inflammatory biomarkers. Most risk factors and biomarkers had associations that attenuated with increasing age at onset. Some biomarkers had similar CVD age association, while a few had no association with CVD onset at any age. Conclusions These findings showed that diabetes and insulin resistance, in addition to hypertension, metabolism syndrome, overweight or obese, dyslipidemia, and smoking, appeared to be the strongest risk factors for premature onset of CVD, and most risk factors had attenuated relative rates at older ages.